MATERIAL PROCESS IN TRANSITIVITY OF BESEMAH LANGUAGE CLAUSES: A Functional Grammar Approach - Sutiono Mahdi (Sosiohumaniora, 2017)
The title of this study is Material Process in Besemah Language Clause: A Functional Grammar Approach. It aimed to find out material processes in Besemah language and to analyze the elements of material processes found in the language. This research discusses three main points: (1) the verbs that can be categorized into material process; (2) the participants involved in the material process; and (3) the clause elements of material process. The approach applied in this study was Functional Grammar Approach (FGA) using descriptive method, employing data source from the book Bahasa Besemah 2, which were then analyzed by using tables to show the elements of material processes. The findings of the study showed that (1) the verbs ngelipat, belajagh, ngandas, ngadum, diagai, ngaduk, beghusiq, etc belong to the verbs of material process, (2) the participants involved in the material process can be actor, goal, recipient, client, range, and instrument, and (3) the circumstance can be place, time, manner, and purpose. The verb clause of material processes may be categorized into be intransitive, monotransitive, and ditransitive verb clause.